What’s the Problem with Substantive Review? - Pfiffer, Megan (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2024)
In Canada (Minister of Citizenship and Immigration) v Vavilov, the Supreme Court of Canada endeavoured to reformulate the law of substantive review of administrative decisions. This was familiar territory for the Court. Over the last four decades, the Court has revised the doctrinal framework for substantive review on numerous occasions, with limited success in promoting stability in the law. Early academic responses to Vavilov considered whether the new doctrinal framework would endure. This paper focuses on a prior question: What is the problem with substantive review? It argues that contrary to the Court’s longstanding position, the foundations of the law of substantive review are neither clear nor stable. Rather, substantive review doctrine is built upon two heavily contested principles capable of being conceptualized in different ways. The jurisprudence features multiple competing conceptions of those principles, producing tensions which create instability in the law. This suggests that to solve the problem, a coherent theory of substantive review that either resolves or prevents these tensions is necessary.